1995
DOI: 10.1146/annurev.pc.46.100195.001513
|View full text |Cite
|
Sign up to set email alerts
|

External Infrared Reflection Absorption Spectrometry of Monolayer Films at the Air-Water Interface

Abstract: The theory and practice of external infrared reflection absorption spectrometry (IRRAS) as applied to monomolecular films at the air-water interface are reviewed. The observed IR frequencies for films of amphiphilic species provide information about the conformational states of the hydrocarbon chains and the hydrogen bonding and ionization states of the polar head groups, under conditions of controlled surface pressure. Determination of molecular orientation is also feasible and requires detailed consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
438
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(450 citation statements)
references
References 0 publications
10
438
1
1
Order By: Relevance
“…Peak positions of CH 2 vibrational modes are sensitive to the conformational order of the alkyl chains, and can provide insight into the relative number of trans and gauche conformations in the monolayer; i.e., a shift to lower wavenumbers indicates that the alkyl chains have more trans bonds. [19,56] It was observed that, during the transition from the LE-LC phase to the LC phase in the DPPC monolayer on pure water, the symmetric CH 2 stretching frequency decreased from 2855 to 2851 cm À1 and the asymmetric CH 2 stretch decreased from 2924 to 2919 cm À1 , indicating an increase in trans relative to gauche conformations and a higher degree of order. [19,37] Such a trend can be observed in Table 1, where the vibration modes of CH 3 asymmetric (u a (CH 3 )), CH 2 asymmetric (u a (CH 2 )), CH 3 symmetric (u s (CH 3 )) and CH 2 symmetric (u s (CH 2 )) at 2955, 2919, 2880 and 2850 cm À1 , respectively, are shifted to lower wavenumbers when DPPC is compressed on the Na 2 SO 4 solution.…”
Section: Conformation Of the Alkyl Chain In The Dppc Monolayermentioning
confidence: 99%
“…Peak positions of CH 2 vibrational modes are sensitive to the conformational order of the alkyl chains, and can provide insight into the relative number of trans and gauche conformations in the monolayer; i.e., a shift to lower wavenumbers indicates that the alkyl chains have more trans bonds. [19,56] It was observed that, during the transition from the LE-LC phase to the LC phase in the DPPC monolayer on pure water, the symmetric CH 2 stretching frequency decreased from 2855 to 2851 cm À1 and the asymmetric CH 2 stretch decreased from 2924 to 2919 cm À1 , indicating an increase in trans relative to gauche conformations and a higher degree of order. [19,37] Such a trend can be observed in Table 1, where the vibration modes of CH 3 asymmetric (u a (CH 3 )), CH 2 asymmetric (u a (CH 2 )), CH 3 symmetric (u s (CH 3 )) and CH 2 symmetric (u s (CH 2 )) at 2955, 2919, 2880 and 2850 cm À1 , respectively, are shifted to lower wavenumbers when DPPC is compressed on the Na 2 SO 4 solution.…”
Section: Conformation Of the Alkyl Chain In The Dppc Monolayermentioning
confidence: 99%
“…The principle of the method and its application to Langmuir films at the air-water interface are described elsewhere. 11 The spectra were acquired with an IFS 66 FT-IR spectrometer from Bruker (Ettlingen, Germany), which is equipped with an external reflectance unit (XA -511, Bruker) containing a Langmuir trough setup. The incidence angle is adjustable due to a computer-driven rotation of a mount, which contains a series of mirrors.…”
Section: Irra Spectroscopymentioning
confidence: 99%
“…To compensate residual water vapour rotation-vibration bands a Langmuir trough consisting of two parts was used. [11][12] One part was covered by the monolayer (sample), the other one is monolayer-free (reference). Both parts are connected to ensure the same surface height.…”
Section: Irra Spectroscopymentioning
confidence: 99%
“…ATR is now among the most useful tools to characterize biological films supported by solid crystals [55,56]. As a method to probe biointerfaces, IRRAS had its applicability largely expanded when it was adapted to Langmuir monolayers [57,58].…”
Section: Infrared Absorption-based Spectroscopic Methodsmentioning
confidence: 99%